Superconductivity Basics and Applications to Magnets - Sharma, R.G (Springer Series in Materials Science,, 2015)
This book presents the basics and applications of superconducting magnets. It explains the phenomenon of superconductivity, theories of superconductivity, type II superconductors and high-temperature cuprate superconductors. The main focus of the book is on the application to superconducting magnets to accelerators and fusion reactors and other applications of superconducting magnets. The thermal and electromagnetic stability criteria of the conductors and the present status of the fabrication techniques for future magnet applications are addressed. The book is based on the long experience of the author in studying superconducting materials, building magnets and numerous lectures delivered to scholars. A researcher and graduate student will enjoy reading the book to learn various aspects of magnet applications of superconductivity. The book provides the knowledge in the field of applied superconductivity in a comprehensive way.